The Effects of Estrogen Receptors' Antagonist on Brain Edema, Intracranial Pressure and Neurological Outcomes after Traumatic Brain Injury in Rat - Dehghan, Fatemeh (Iran Biomed J, 2015)
BACKGROUND: In previous studies, the neuroprotective effect of 17β-estradiol in diffuse traumatic brain injury has been shown. This study used ICI 182,780, a non-selective estrogen receptor antagonist, to test the hypothesis that the neuroprotective effect of 17β-estradiol in traumatic brain injury is mediated by the estrogen receptors. METHODS: The ovariectomized rats were divided into eight groups. Brain injury was induced by Marmarou’s method. Estrogen was injected 30 minutes after traumatic brain injury, and ICI 182,780 was injected before traumatic brain injury and also before estrogen treatment. In one group only ICI 182,780 was injected. The brain water content and Evans blue dye content were measured 24 and 5 hours after traumatic brain injury, respectively. The neurologic outcomes and intracranial pressure were assessed before, 4, and 24 hours after traumatic brain injury. RESULTS: Brain water content and Evans blue content were less in estrogen-treated group comparison to vehicle group. ICI 182,780 eliminated the effects of estrogen on brain edema and brain blood barrier permeability. Intracranial pressure was increased significantly after trauma, and estrogen decreased intracranial pressure at 4 and 24 hours after traumatic brain injury in comparison to vehicle. This inhibitory effect was also eliminated by treatment with ICI182,780. ICI 182,780 also inhibited the estrogen induced increase in neurologic outcomes following traumatic brain injury. However, the use of ICI 182,780 alone had no neuroprotective effect after traumatic brain injury. CONCLUSION: The results suggest that classical estrogen receptors have probably a role in the neuroprotective function of estrogen following traumatic brain injury.